A novel Alu-like element rearranged in the dystrophin gene causes a splicing mutation in a family with X-linked dilated cardiomyopathy. - Ferlini, A (1998)
We have identified and characterized a genomic sequence with some features typical of Alu-like mobile elements rearranged into the dystrophin gene in a family affected by X-linked dilated cardiomyopathy. The Alu-like sequence rearrangement occurred 2.4 kb downstream from the 5' end of intron 11 of the dystrophin gene. This rearrangement activated one cryptic splice site in intron 11 and produced an alternative transcript containing the Alu-like sequence and part of the adjacent intron 11, spliced between exons 11 and 12. Translation of this alternative transcript is truncated because of the numerous stop codons present in every frame of the Alu-like sequence. Only the mutant mRNA was detected in the heart muscle, but in the skeletal muscle it coexisted with the normal one. This result is supported by the immunocytochemical findings, which failed to detect dystrophin in the patient's cardiac muscle but showed expression of a reduced level of protein in the skeletal muscle. Comparative analysis of the Alu-like sequence showed high homology with other repeated-element-containing regions and with several expressed sequence tags. We suggest that this Alu-like sequence could represent a novel class of repetitive elements, reiterated and clustered with some known mobile elements and capable of transposition. Our report underlines the complexity of the pathogenic mechanism leading to X-linked dilated cardiomyopathy but suggests that differences in tissue-specific expression of dystrophin mutations may be a common feature in this condition.